Manganese transporter genetics and sex modify the association between environmental manganese exposure and neurobehavioral outcomes in children. (September 2019) - Broberg, Karin; Taj, Tahir; Guazzetti, Stefano; Peli, Marco; Cagna, Giuseppa; Pineda, Daniela; Placidi, Donatella; Wright, Robert O.; Smith, Donald R.; Lucchini, Roberto G.; Wahlberg, Karin
Abstract: There is increasing evidence that environmental manganese (Mn) exposure early in life can have negative effects on children's neurodevelopment and increase the risk of behavioral problems, including attention deficit hyperactivity disorder (ADHD). Factors that may contribute to differences in sensitivity to Mn exposure are sex and genetic variation of proteins involved in the regulation of Mn concentrations. Here we investigate if sex and polymorphisms in Mn transporter genes SLC30A10 and SLC39A8 influence the association between Mn exposure and ADHD-related behavioral problems in children. The SNPs rs1776029 and rs12064812 in SLC30A10, and rs13107325 in SLC39A8 were genotyped by TaqMan PCR or pyrosequencing in a population of Italian children (aged 11–14 years; n = 645) with a wide range of environmental Mn exposure. Mn in surface soil was measured in situ using XRF technology or modeled by geospatial analysis. Linear regression models or generalized additive models (GAM) were used for analyzing associations between soil Mn and neurobehavioral problems assessed by the Conners' behavior rating scales (self-, and parent-reported). Gene-environment interactions (Mn transporter genotype x soil Mn) were evaluated using a genetic score in which genotypes for the three SNPs were combined based on their association with blood Mn, as an indication of their influence on Mn regulation. We observed differences in associations between soil Mn and neurobehavior between sexes. For several self-reported Conners' scales, girls showed U-shaped relationships with higher (worse) Conners' scoring at higher soil Mn levels, and several parent-reported scales showed positive linear relationships between increasing soil Mn and higher Conner's scores. For boys, we observed a positive linear relationship with soil Mn for one Conner's outcome only (hyperactivity, parent-reported). We also observed some interactions between soil Mn and the genetic score on Conner's scales in girls and girls with genotypes linked to high blood Mn showed particularly strong positive associations between soil Mn and parent-reported Conners' scales. Our results indicate that sex and polymorphisms in Mn transporter genes contribute to differences in sensitivity to Mn exposure from the environment and that girls that are genetically less efficient at regulating Mn, may be a particularly vulnerable group. Highlights: Influence of sex and genetics on Mn exposure vs neurobehavior was evaluated. Stronger associations between soil Mn and behavioral problems in girls than boys SNPs in Mn transporter genes influenced sensitivity to Mn exposure in girls. Girls with inefficient Mn regulation may be particularly sensitive to Mn exposure.